2018
DOI: 10.1101/314674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grapevine virus L: a Novel Vitivirus in Grapevine

Abstract: Vitivirus is a genus within the family Betaflexiviridae (Tymovirales) of ssRNA(+) viruses. There are currently ten ICTV recognized virus species in the genus; nevertheless, the extended use of NGS technologies is rapidly expanding their diversity and six more have been proposed recently. Here, we present the in silico characterization of a novel virus detected in grapevine (cv Riesling) which fits the genomic architecture and evolutionary constraints to be classifiable within the Vitivirus genus. The detected … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…NGS of siRNAs was used by Maliogka et al [141] to initially detect Grapevine Roditis leaf discoloration-associated virus (GRLDaV) Badnavirus. The list of the new grapevine viruses detected using the NGS technique is quickly growing, due to recent studies [8][9][10][11]134]. However, this is only the first step in the study of new viral diseases, which should be followed by an assessment of the contribution of the virus to the development of symptoms, the study of its biology and ecology, the need to correct regulatory documents and certification schemes.…”
Section: Next-generation Sequencing: a New Approach To Viral Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…NGS of siRNAs was used by Maliogka et al [141] to initially detect Grapevine Roditis leaf discoloration-associated virus (GRLDaV) Badnavirus. The list of the new grapevine viruses detected using the NGS technique is quickly growing, due to recent studies [8][9][10][11]134]. However, this is only the first step in the study of new viral diseases, which should be followed by an assessment of the contribution of the virus to the development of symptoms, the study of its biology and ecology, the need to correct regulatory documents and certification schemes.…”
Section: Next-generation Sequencing: a New Approach To Viral Diagnosismentioning
confidence: 99%
“…As of 2017 [7], there were more than 70 virus species belonging to 17 families and 27 genera that can cause grapevine diseases. This figure is constantly growing due to the use of next generation sequencing fir the identification of new pathogenic species (see Section 7) [8][9][10][11]. Disease symptoms caused by pathogenic grapevine viruses vary widely including reduced growth and development of the plant, leaf spotting, chlorosis, necrosis, streaking and ring-shaped spots on the leaves, leaf curling, leaf discoloration (yellowing or reddening), wrinkling, pitting or grooving of wood and swelling at the grafting site [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2019, two more proposed vitiviruses were discovered in grapevine. Grapevine virus L (GVL) was initially identified in RNAseq data and later detected in multiple plants in Croatia, New Zealand and the United States [ 2 ]. Grapevine virus M (GVM) was also discovered by high throughput sequencing (HTS) in an American hybrid grapevine [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grapevine virus L (GVL) is a new member of the genus Vitivirus in the family Betaflexiviridae, which was recently identified with the application of high throughput sequencing (Debat et al 2019). Even though other well-known vitiviruses such as grapevine virus A (GVA), grapevine virus B (GVB) and grapevine virus D (GVD) were previously reported in Turkish vineyards (Cigsar et al 2002, Buzkan et al 2017, no information exists on the occurrence of the newly identified GVL.…”
mentioning
confidence: 99%